ANALISIS POTENSI DAN DAMPAK KEBOCORAN GAS HIDROGEN PADA HYDROGEN PLANT DI INDUSTRI PELUMAS - Setiawan, Adhi; Hanifah, Dian Nur; Nugroho, Agung; Dermawan, Denny (Universitas Nahdlatul Ulama Sidoarjo, 2017)
Increasing the need for pure hydrogen in the industry is growing. One of its roles is in purification of petroleum industry. High purity hydrogen (99.99%) was obtained from methane using the steam methane reforming method in the hydrogen plant unit. Hydrogen is a very dangerous chemical element with its flammable properties. This research is conducted especially on purification system. Quantitative analysis is used to determine the frequency of hydrogen leakage, consequence modeling, and risk estimation that will be generated. The results of the analysis show that the highest frequency occurs in unignited release events. The jet fire scenario produces the longest fire length in the HPU about 27 meters. The jet fire scenario impact produces the farthest secure distance in the case of a leak in the HPU section of 60 meters. The flash fire produces the farthest distance loss in a leakage case in the HPU of 80 meters, and explosion at a radius of 200 meters will have a blast overpressure 7.62 psig with 22% fatality estimation of the population.